Care Management to Reduce Disparities and Control Hypertension in Primary Care: A Cost-effectiveness Analysis. Issue 2 (February 2018) - Hong, Jonathan C.; Padula, William V.; Hollin, Ilene L.; Hussain, Tanvir; Dietz, Katherine B.; Halbert, Jennifer P.; Marsteller, Jill A.; Cooper, Lisa A.
Abstract : Background: Project ReD CHiP (reducing disparities and controlling hypertension in primary care) care management was a clinic-based intervention that aimed to improve blood pressure control through improved care coordination and provide self-management support to patients from racially and socioeconomically. Objective: To evaluate the cost-effectiveness of ReD CHiP care management versus standard care to treat hypertension in diverse communities. Research Design: Microsimulation model from a health care sector perspective over 15 years. We used the published literature to inform our model including the ReD CHiP trial and the age-specific and race-specific cardiovascular disease risk equations. Deterministic and probabilistic sensitivity analyses were conducted to assess the uncertainty. Subjects: Primary prevention in a racially diverse setting. Measures: Costs per quality-adjusted life years (QALYs) to produce an incremental cost-effectiveness ratio (ICER). Results: ReD CHiP had an increase of $2114 and 0.04 QALYs. The ICER was $52, 850/QALY. Predominately African American (ICER: $48, 250/QALY) and elderly populations (ie, age 65+) derived value from ReD CHiP (ICER: $39, 525/QALY). The value of ReD CHiP varied with changes in the reduction in systolic blood pressure (5 mm Hg reduction, ICER: $133, 300/QALY; 15 mm Hg reduction, ICER: $18, 767/QALY). Probabilistic sensitivity analysis indicated that ReD CHiP CM was cost-effective in over 90% of simulations, based on a willingness-to-pay of $100, 000/QALY. Conclusions: ReD CHiP care management is cost-effective to prevent negative consequences of hypertension. African American and elderly patients have more favorable ICERs, recommending targeted interventions to improve health equity among vulnerable patient populations. Abstract : Supplemental Digital Content is available in the text.